Examining the Role of Social Support in Mitigating Psychological Distress among Families of Murder Victims during Court Trials: A Qualitative Study - Waqas Ahmed; Dr. Nazi Iqbal (Journal of Peace, Development and Communication, 2023)
This research paper examines the critical role of social support in mitigating psychological distress among families of murder victims throughout court trials. It investigates the relationship between social support and psychological distress, with a particular emphasis on comprehending how different forms of support can impact the well-being of these families. The study employs a qualitative research approach, utilizing in-depth interviews to gather data from a sample of families (n=7) who have tragically experienced the loss of a loved one due to murder. According to the study, these families face despair, anxiety, post-traumatic stress disorder, and complex grieving. However, there is little research on how social support reduces psychological discomfort in Punjab, Pakistan court proceedings. Thematic analysis of the interview underscores the significance of emotional, informational, and instrumental support in enhancing the well-being and resilience of these families throughout the demanding legal process. These findings underscore the necessity for customized care for murder victims' families. These findings can help professionals to devise support strategies for such families, throughout proceedings.